Pengukuran Kinerja RSUD Dr. Saiful Anwar Melalui Metode Balanced Scorecard - Erni Mitrawati; Edi Subiyantoro; Harmono Harmono (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2018)
The purpose of research to find out the performance measurement of RSUD Dr. Saiful Anwar through Balanced Scorecard method. The research method used in this research using mixed methods approach. The result of research shows that the measurement of public performance based on Balanced Scorecard method of RSUD Dr.Saiful Anwar Malang 2014 - 2016 is divided into 4 approaches: customer approach, financial approach, approach with internal business process and overall learning & growth are included in good performance. The performance of hospitals Dr.Saiful Anwar Malang in the perspective of customers included in the category very well with the value reached 83.28, Performance RSUD Dr.Saiful Anwar Malang in the financial perspective included in the category good, Performance RSUD Dr.Saiful Anwar Malang in the perspective of internal business processes including in good category, and the performance of RSUD Dr.Saiful Anwar Malang in perspective of Learning & Growth included in good category, so it can be said that RSUD Dr.Saiful Anwar Malang able to increase employee capability and employee commitment.